HEALTH CARE IN PEDIATRIC EMERGENCIES - da Silva Santos, Samara; Dayanna Alves Resende, Tamires; Kelly da Silva, Nathalia; da Silva Carvalho, Denise; Gomes De Souza Silva, Lúcia; Carolina Salustino dos Santos, Maria; Claudino do Nascimento , Nathalia (Health and Society, 2022)
In pediatric emergencies, care is defined according to the priority of the cases, analyzed from a triage in order to filter this priority, as an urgency or emergency, based on the complaints and the clinical scenario of the patients. Study of reflective origin, built in 2022, through a combination of readings. Thus, there are numerous factors that place the child in risk situations. The main causes of emergency care in pediatric care units include respiratory diseases, convulsive states, poisoning, accidents and trauma.